Reading Attitude Scale: Validity and Reliability Study - İbrahim Halil Yurdakal; Fatma Susar Kırmızı (Elementary Education Online, 2023)
In this study, an attitude scale related to reading was developed and validity and reliability studies were conducted. In the field, there were many attitude scales for reading and very few studies were found at the fourth grade level of elementary school. In this context, in order to determine primary school fourth graders attitudes towards reading, 32 fourth grade primary school students opinions about attitudes towards reading were taken with semi-structured interview form. Using the obtained qualitative data, a draft scale of 58 items was prepared. The number of items has been reduced to 54 after expert opinion. Six field specialists, three primary school teachers and two Turkish language teachers opinions were taken. The pretesting was made with 72 students and analyzing the materials. For the pilot application, student scale was applied up to 5 times (270) items. The obtained data were analyzed by SPSS 23 packet program. Before the analysis, the scale was subtracted from the extreme values and 9 scale form was extracted from the analysis based on Mahalanobis distance values. The KMO value of the scale is 0.817 and it can be said that the sample is sufficient for analysis. After the exploratory factor analysis, the scale consists of 4 dimensions. Substance load values of the substances in the first dimension are 0.511-0.768; the items in the second dimension are 0.353-0.616; 0.461-0.690 for the items in the third dimension and 0.372-0.592 for the items in the fourth dimension. The Spearman-Brown correlation coefficient is 0.81 and this value is sufficient in terms of two half reliability. It can be said that the level of internal consistency is high according to this value. Cronbach's Alpha score of scale is 0.853. The final scale consists of 4 dimensions and 28 questions